Neural based sliding-mode control with moving sliding surface for the seismic isolation of structures - Yakut, Oguz; Alli, Hasan (Sage Publications Ltd, 2011)
The neural based sliding-mode control method is developed by using advantageous specifications of sliding-mode control and artificial neural network techniques and applied to an eight storey sample building with active tendon. Success of the designed controller is examined by applying acceleration data belonging to six different earthquakes as the external driving source. A MATLAB package program is used for numerical solutions, and the obtained results are compared in graphical form, presented in tables. For the optimization process, genetic algorithm is used. In this study parametric uncertainties and time delay effects are also considered. It is seen that the success of the controller is quite high and the control force can be used for real applications. Furthermore, the obtained results indicate that the controller provides quite successful control under earthquake having different characteristics.
Keywords: Active control of structures; artificial neural networks; earthquake-excited structures; genetic algorithm; moving sliding surface; sliding-mode control